Sport participation motives of young Brazilian judo athletes - Dartagnan Pinto Guedes; Marcelo Seiji Missaka (Universidade Estadual Paulista (UNESP), 2015)
The objective of this study was to identify the motives for sport participation in a sample of young judo athletes according to sex, age, and training history. A total of 392 subjects aged 12 to 18 years old participated in the study. Portuguese version of the Participation Motivation Questionnaire was used to identify motives for sports participation. Boys reported giving significantly more importance to sports participation in terms of Competition and Skill Development, whereas girls presented significantly higher ratings for Teamwork and Friendship. Motivational factors related to Achievement/Status and Fun presented significantly higher average ratings in younger judo athletes, whereas average ratings of Competition significantly increased with increasing age. Average ratings related to Fitness, Competition and Skill Development were proportionally and significantly higher according to training experience and training volume. These results will contribute to establishing intervention programs designed to reduce sport dropout rates among young judo athletes.